2011
DOI: 10.3390/ijms12021009
|View full text |Cite
|
Sign up to set email alerts
|

Role of Versican, Hyaluronan and CD44 in Ovarian Cancer Metastasis

Abstract: There is increasing evidence to suggest that extracellular matrix (ECM) components play an active role in tumor progression and are an important determinant for the growth and progression of solid tumors. Tumor cells interfere with the normal programming of ECM biosynthesis and can extensively modify the structure and composition of the matrix. In ovarian cancer alterations in the extracellular environment are critical for tumor initiation and progression and intra-peritoneal dissemination. ECM molecules inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 118 publications
0
92
0
2
Order By: Relevance
“…The majority of HA is localized in tumor ECM, where it binds with multiple hyaladherins or hyalectans (5,6,37,38). Versican is predominantly expressed in HA high tumors (5,37,38) and has limited commercial availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of HA is localized in tumor ECM, where it binds with multiple hyaladherins or hyalectans (5,6,37,38). Versican is predominantly expressed in HA high tumors (5,37,38) and has limited commercial availability.…”
Section: Discussionmentioning
confidence: 99%
“…Versican is predominantly expressed in HA high tumors (5,37,38) and has limited commercial availability. Aggrecan is a proteoglycan with structure composition similar to versican and binds to HA efficiently and was used in the in vitro studies reported here.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, versican expression correlates with a poor prognosis in many cancer types (301,325). This proteoglycan interacts with multiple ECM and cell surface components, promoting cell proliferation, cell motility, and metastasis (301,310,382). Intriguingly, in breast cancer, versican has been associated with chemotherapy resistance related to EGFR hypersignaling and enhanced cancer cell self-renewal (78,79).…”
Section: Proteoglycansmentioning
confidence: 99%
“…In general, accumulation of HA in tissues where it is normally absent facilitates tumor growth (i.e., gastric cancers), while reduced HA is associated with cancer in normally HArich stratified epithelia containing tissues such as skin, mouth, and larynx (355). Interestingly, epithelial HA accumulation in colon cancer constitutes a bad prognostic occurrence (304), while stromal HA buildups have been associated with an unfavorable prognosis in ovarian, prostate, breast, and nonsmall cell lung cancers (11,217,289,382). In the case of liver, the main organ in charge of processing HA (98), a large synthesis of the glycosaminoglycan and increasing circulating levels of HA have been found to correlate with liver fibrosis (cirrhosis) (280).…”
Section: Hyaluronanmentioning
confidence: 99%
“…However, an emerging theme is that many such structural proteoglycans have, in addition, signaling roles, particularly with respect to the immune system. Versican has been identified as upregulated in many tumors, including, lung, gastric, ovarian, breast, and melanoma (Kim S et al 2009;Ricciardelli et al 2009;Du et al 2010;Ween et al 2011, Hernández et al 2011. In 2009, it was identified as a macrophage activator, through cell surface TLR2:TLR6 complexes that in turn induced TNF-α secretion by myeloid cells, with downstream promotion of lung cancer metastasis (Kim S et al 2009).…”
Section: Proteoglycans and Acquired Diseasesmentioning
confidence: 99%